Preparing caregivers for dehospitalization of technology-dependent patients: perspective of Home Care professionals - Daniela Miyuki Sato; Elen Ferraz Teston; Gleice Kelli Santana de Andrade; Sonia Silva Marcon; Bianca Cristina Ciccone Giacon-Arruda; Joice Lourenço da Silva; Sueli Aparecida Frari Galera (Universidade Federal do Ceará, 2022)
Objective: to know how the preparation of caregivers of technology-dependent patients is conducted from the perspective of professionals from the Home Care Service. Methods: a qualitative study, conducted with nine professionals from the Home Care Service teams. The data was collected through semi-structured interviews and submitted to Content Analysis, thematic modality. Results: two categories emerged: Strategies and resources used in the preparation of caregivers for dehospitalization and Factors that influence the preparation of caregivers for dehospitalization, which show that this preparation involves the use of soft technologies, based on the interaction and valorization of learning, besides aspects related to the organization of the service in the intra-hospital and home contexts. Conclusion: the preparation of caregivers is permeated with concern for facilitating the acquisition of knowledge and skills for care at home; it involves the use of specific resources and strategies and is influenced positively by technologies and negatively by factors related to hospital structure and organization. Contributions to practice: the findings of the study can subsidize the practices of multiprofessional teams working in the home scenario, since they point out aspects that facilitate and hinder the preparation/training of caregivers.